Redefining Corporate Social Risk Mitigation Strategies - Zandvliet, Luc (World Bank, Washington, DC, 2012)
This note looks at how companies engage with stakeholders in areas with high social or political tensions. It argues that most social risk-mitigation strategies often exacerbate tensions and risks to the companies. The note offers a checklist of risk indicators and a set of questions companies can use to gauge the state of relations with communities and other stakeholders. The real risk to corporations is not whether they take measures to benefit local communities, but the types of relations they build-not so much what they do, but rather how they do it.